1980
DOI: 10.1097/00006842-198011000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Type A Behavior, Hostility, and Coronary Atherosclerosis*

Abstract: Type A behavior pattern was assessed using the structured interview and hostility level was assessed using a subscale of the Minnesota Multiphase Personality Inventory in 424 patients who underwent diagnostic coronary arteriography for suspected coronary heart disease. In contrast to non-Type A patients, a significantly greater proportion of Type A patients had at least one artery with a clinically significant occlusion of 75% or greater. In addition, only 48% of those patients with very low scores (less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
246
1
5

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(271 citation statements)
references
References 17 publications
19
246
1
5
Order By: Relevance
“…Hostile individuals have been described as creating a self-fulfilling prophecy by not only responding to everyday stressors with heightened physiological reactivity, but also reinforcing negative interactions with other people through cynical attitude, increasing the probability of subsequent stressful interactions (Smith & Pope, 1990). The Ho scale was found to provide a stronger association to severity of coronary artery disease (CAD) among patients undergoing coronary angiography than the association between Type A behavior assessments and CAD in the same sample (Williams et al, 1980). Numerous studies have established a relationship between the Ho scale and coronary dysfunction.…”
Section: Hostility Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hostile individuals have been described as creating a self-fulfilling prophecy by not only responding to everyday stressors with heightened physiological reactivity, but also reinforcing negative interactions with other people through cynical attitude, increasing the probability of subsequent stressful interactions (Smith & Pope, 1990). The Ho scale was found to provide a stronger association to severity of coronary artery disease (CAD) among patients undergoing coronary angiography than the association between Type A behavior assessments and CAD in the same sample (Williams et al, 1980). Numerous studies have established a relationship between the Ho scale and coronary dysfunction.…”
Section: Hostility Assessmentmentioning
confidence: 99%
“…Since this study investigated coronary calcification in individuals 18-30 yrs of age, these results suggest that a high level of trait hostility may predispose young adults to CHD. Another study utilizing 424 angiography patients revealed that 70% of those with Ho scores above 10 had clinically significant CAD (Williams et al, 1980). One problem in reviewing studies that directly link the Ho scale to coronary pathology is the difficulty in determining direction of causality.…”
Section: Hostility Assessmentmentioning
confidence: 99%
“…Hostility also has been linked to the severity of ooronary atherosolerosis (Williams, Haney, Lee, Kong, Blumenthal, & Whalen, 1980;Shekelle, Gale, Ostfeld, & Paul, 1983;Barefoot, Dahlstrin & Williams, 1983), although the differentiation between anger and hostility in the literature seldom has been clear. Cook & Medley (1954) (1979) found that men who scored high in denial, compared to those low in denial, showed marginally greater heart rate, increased spontaneous skin resistance and significantly greater frontalis region EMG.…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%
“…Spielberger has described state anger as "an emotional state or condition that consists of subjective feelings of tension, annoyance, irritation, fury and rage, with concomitant activation or arousal of the autonomic nervous system" (Spielberger, 1988, The Cook-Medley Hostility (HO) Scale (Cook & Medley, 1954), a 50 item hostility inventory, has also been found frequently to be associated with coronary heart disease outcomes (e.g., Barefoot, Dahlstrom, & Williams, 1983, Williams et al, 1980Williams et al, 1985;Shekelle et al, 1983). It will also be utilized in an attempt to assess whether the factors it measures are similar to or different from those of the STAXI.…”
Section: Cardiovascular Reactivity 29mentioning
confidence: 99%
“…Aunque para ser más exactos, deberíamos hablar del componente irahostilidad del PCTA (Barefoot et al, 1983;Dembroski et al, 1989;Hecker, Chesney, Black, & Frautschi, 1988;King, 1997;MacDougall, Dembroski, Dimsdale, & Hackett, 1985;Richter et al, 2011;Shekelle et al, 1983;Williams et al, 1980). En general, existe una gran confusión entre los términos ira y hostilidad, siendo éstos en ocasiones empleados como sinónimos, sin serlo; en el siguiente apartado, se detallará más a este respecto.…”
Section: A12 El Constructo Ira-hostilidad El Nuevo Patrón De Predunclassified